Does believing something to be fiction allow a form of moral licencing or a 'fictive pass' in understanding others' actions? - Thompson, J; Teasdale, B; van Emde Boas, E; Budelmann, F; Duncan, S; Maguire, L; Dunbar, R (Frontiers Media, 2023)
Introduction: The human capacity to engage with fictional worlds raises important psychological questions about the mechanisms that make this possible. Of particular interest is whether people respond differently to fictional stories compared to factual ones in terms of how immersed they become and how they view the characters involved and their actions. It has been suggested that fiction provides us with a ‘fictive pass’ that allows us to evaluate in a more balanced, detached way the morality of a character’s behaviour. Methods: We use a randomised controlled experimental design to test this. Results and discussion: We show that, although knowing whether a substantial film clip is fact or fiction does not affect how engaged with (‘transported’ by) a troubling story an observer becomes, it does grant them a ‘fictive pass’ to empathise with a moral transgressor. However, a fictive pass does not override the capacity to judge the causes of a character’s moral transgression (at least as indexed by a causal attribution task).